PERANCANGAN APLIKASI PEMBELAJARAN PENGENALAN NAMA WARNA BERBASIS MULTIMEDIA DI TK LESTARI DESA TAMAONA - Hilmatul Wahda; Raden Wirawan; muhammad awal nur (LPPM STMIK BINA ADINATA, 2021)
This research aims to designing apps to learn to know colors in children and implement a color name recognition learning app for children with basic color merging.Research method in the design of multimedia-based color recognition learning application using Multimedia development method Luther-Sutopo Version multimedia development life cycle (MDLC) with Concept stage, Design using Macromedia Flash Fropessional 8.0, Material Collecting, Assembly, and Testing using Black Box. The method of data collection in research with the stages of Observation, Interview, and Study Library..The results of this multimedia-based color recognition learning application conclude that : (1) Has been designed multimedia-based color recognition learning application for teaching learning process in Lestari Kindergarten Tamaona Village, especially to recognize basic colors, secondary colors, and tertiary colors in indonesia and english that can help teachers in conveying their materials, with this learning medium children more easily recognize colors, (2) It has facilities in primary, secondary and tertiary color recognition learning applications provided in the form of images, animations and sounds, as well as a game that contains questions related to getting to know primary, secondary and tertiary colors